Reactive oxygen species inhibitors block priming, but not activation of the NLRP3 inflammasome - Bauernfeind, Franz (2011)
A common denominator among the multiple damage-inducing agents that ultimately lead to the activation of NLRP3 has not yet been identified. Recently, the production of reactive oxygen species (ROS) has been suggested to act as a common event upstream of the NLRP3 inflammasome machinery. Since de novo translation of NLRP3 is an essential step in the activation of NLRP3, we investigated the role of substances that either inhibit ROS production or its oxidative activity. While we observe that NLRP3 inflammasome activation is unique amongst other known inflammasomes due to its sensitivity to ROS inhibition, we have found that this phenomenon is attributable to the fact that NLRP3 strictly requires priming by a pro-inflammatory signal, a step that is blocked by ROS inhibitors. While these data do not exclude a general role of ROS production in the process of NLRP3-triggered inflammation, they put ROS upstream of NLRP3 induction, but not activation.